(untitled) (Research, Society and Development, 2021)
The third molars when misaligned, can cause complications for the patient, and in practice, especially in oral surgery and orthodontic field.This study aims to analyze changes in the shape and size of the jaw bone structure associated with the impact of third molars from geometric morphometry.This is a cross-sectional study, carried out with 110 panoramic radiographs of patients aged 18 to 25 years, attended at the Dentistry Module of the State University of Southwest Bahia. After obtaining panoramic radiographic images, measurements were made, followed by the generalized analysis of Procrustes, Discriminant function, cross-validation and Mahalanobis distance. There was no significant difference in the size of the mandible between the genders of the groups with and without impacted third molars (p> 0.05). For the shape of the mandible, significant differences (p <0.05) were identified between the groups. Panoramic radiographs of individuals with impacted teeth were correctly classified 67.1% of the time, while in the control group 52.4%. The Mahalanobis distance showed significant differences (p <0.05) between radiographs of individuals with and without impacted third molars. Based on the outline, the radiographs of patients with impacted teeth show expansion in the mental region and compression in the condyle of the mandible.It was concluded that there are changes in the shape of the mandible, especially in the mental region and the condyle, and this may be associated with the impact of third molars.